Quantitative ethnobotany of medical plants in non-indigenous communities of Loboc, Bohol, Philippines - Beloy, Iresh; Oclarit, Jairyl; Naypa, Junry; Lomosbog, Noel T. (Ethnobotany Research and Applications, 2026)
Background: Ethnobotanical knowledge among non-indigenous populations remains underdocumented, limiting our understanding of the role traditional medicine plays in rural Philippine healthcare. This study aimed to quantitatively assess and compare ethnomedicinal plant knowledge in two non-indigenous barangays, Gon-ob and Buenavista, in Loboc, Bohol, Philippines. Methods: Semi-structured interviews were conducted with 146 respondents to document the use of medicinal plants. Four quantitative ethnobotanical indices, Use Value (UV), Relative Frequency of Citation (RFC), Informant Consensus Factor (ICF), and Fidelity Level (FL), were calculated to determine cultural significance, agreement, and specificity of plant use within and between communities. Results: From 146 informants, a total of 42 medicinal plant species belonging to 27 families were recorded, with Euphorbiaceae being the most represented. While several species were commonly used in both communities, differences were observed in use values, relative frequency of citation, preparation methods, and ailment-specific consensus between Gon-ob and Buenavista. Halib-on (Blumea balsamifera), kalabo (Coleus amboinicus), and lagundi (Vitex negundo) exhibited the highest UV and RFC values, underscoring their importance in community health traditions. Leaves were the most frequently used plant parts, and decoction was the predominant preparation method. High ICF values for respiratory and skin ailments indicated a strong, yet community-specific, consensus among informants. Conclusions: The study provides baseline quantitative evidence of both shared and distinct ethnomedicinal practices between two non-indigenous rural communities in Bohol, highlighting culturally significant species that warrant prioritization in future research and conservation efforts. In particular, B. balsamifera, C. amboinicus, and V. negundo, identified as the most culturally important species, should be prioritized for focused documentation, sustainable management, and further pharmacological research. Keywords: Bohol, Philippines, Ethnobotanical indices, Ethnomedicinal plant, Non-indigenous local communities, Traditional knowledge